2017
DOI: 10.1111/afe.12265
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shaded systems on Xylosandrus compactus infestation in Robusta coffee along a rainfall gradient in Uganda

Abstract: 1 We investigated the relationship between characteristics of coffee shade systems and coffee pest infestation by the black coffee twig borer Xylosandrus compactus Eichhoff. The pest deprives Uganda of $40 millions annually, yet its control remains inadequate. 2 The present study considered three rainfall zones in Central Uganda and 50 coffee plots that were randomly selected from each rainfall zone. Data were collected on X. compactus infestation and key shade indicators: canopy cover, tree-species densities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 29 publications
(32 reference statements)
3
27
0
1
Order By: Relevance
“…Shade tree type has been shown to impact significantly the infestation of black coffee twig borer, Xylosandrus compactus (Eichhoff), a pest which severely affects robusta coffee plantations, especially in Uganda (Bukomeko et al 2018). Bukomeko et al (2018) showed that mature shade trees and sap-exuding herbaceous plants such as Carica papaya could significantly reduce black coffee twig borer on robusta coffee plants as well as an increasing number of sap exuding trees (shading level). Impact of 0 to 30% shade on robusta cup taste (on a 0-10 scale) was not significant, yet more than 30% shade reduces it significantly (Vaast and Raghuramulu 2012).…”
Section: Effects Of Shade Trees On Robusta Coffee Quality and Phytosanitary Parameters Without Interacting Factorsmentioning
confidence: 99%
“…Shade tree type has been shown to impact significantly the infestation of black coffee twig borer, Xylosandrus compactus (Eichhoff), a pest which severely affects robusta coffee plantations, especially in Uganda (Bukomeko et al 2018). Bukomeko et al (2018) showed that mature shade trees and sap-exuding herbaceous plants such as Carica papaya could significantly reduce black coffee twig borer on robusta coffee plants as well as an increasing number of sap exuding trees (shading level). Impact of 0 to 30% shade on robusta cup taste (on a 0-10 scale) was not significant, yet more than 30% shade reduces it significantly (Vaast and Raghuramulu 2012).…”
Section: Effects Of Shade Trees On Robusta Coffee Quality and Phytosanitary Parameters Without Interacting Factorsmentioning
confidence: 99%
“…Kondisi tersebut menyebabkan peningkatan serangan X. compactus. Hasil penelitian (Bukomeko, Jassogne, Kagezi, Mukasa, & Vaast, 2017) melaporkan bahwa naungan dan curah hujan berpengaruh nyata terhadap serangan X. compactus pada pertanaman kopi di Uganda.…”
Section: Pendahuluanunclassified
“…A recent meta-analysis on the impact of shade trees on robusta coffee showed that shade trees may enhance yield, growth, and biodiversity, yet few studies tested the effects on pests and diseases to allow a general judgment to be made [19]. Arabica and robusta coffee trees do not have the same ecology [20] and recommended fertilizer rates vary [21], which might alter the shade response [10,18,[22][23][24], and the type of shade trees used [25]. Furthermore, C. arabica and C. canephora may not have the same sensitivity to pests and diseases [26].…”
Section: Introductionmentioning
confidence: 99%